Математична модель неперервної інтерполяції спіралеподібної ДПК за допомогою спеціальної функції - Мацулевич, Олександр Євгенович; Лазарчук-Воробйова, Юлія Валентинівна; Matsulevych, Oleksandr; Lazarchuk-Vorobiova, Yuliia (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: Метою дослідження є аналіз можливостей використання неперервного геометричного моделювання на базі спеціальної функції. Визначенні дотичних у вузлових точках вихідної ДПК при використанні локальних методів згущення. Глобальному призначенні дотичних для алгоритмів згущення замкнених та спіралеподібних ліній. Використання традиційної неперервної інтерполяції часто не дозволяє точно спрогнозувати форму кривої на межах заданого масиву точок, що призводить до необхідності перерахунку параметрів. Для уникнення надлишкових обчислень та акумуляції похибок пропонується впровадження локального методу моделювання з наступним трансформуванням координат у глобальну систему. Запропонована у роботі методика дає можливість застосовувати локальні методи безперервної інтерполяції для ущільнення ДПК. Це реалізується через використання спеціальної інтерполюючої функції. Такий підхід гарантує відсутність небажаної осциляції, забезпечує неперервність перших похідних у місцях з’єднання сегментів моделюючої кривої, а також дозволяє здійснювати глобальне формування дотичних у вузлових точках. /// EN: Continuous modeling is particularly effective for solving problems related to trajectory generation in CNC systems or the search for extreme values. In this case, only the basic reference points are stored in the computer’s memory, while the additional coordinates of the array are calculated dynamically as needed. However, existing methods have significant drawbacks: they do not guarantee the absence of parasitic oscillation (wave-like distortions), and the behavior of the curve on the end segments of the point sequence is often unpredictable. This forces researchers to constantly adjust coefficients and perform repeated calculations. To minimize computational complexity and reduce errors, it is rational to use local modeling methods that involve a subsequent transition to a general (global) coordinate system. The use of traditional continuous interpolation often fails to accurately predict the shape of the curve at the boundaries of a given set of points, which necessitates recalculating the parameters. To avoid excessive computations and the accumulation of errors, we propose the implementation of a local modeling method followed by the transformation of coordinates into a global system. The methodology proposed in this work makes it possible to apply local continuous interpolation methods for DPC densification. This is achieved through the use of a special interpolation function. This approach guarantees the absence of unwanted oscillation, ensures the continuity of first derivatives at the junctions of the modeling curve segments, and also allows for the global formation of tangents at nodal points.
A mathematical model of continuous interpolation of a spiral-shaped dpc using a special function
Keywords: спіралеподібна дискретно представлена крива; супроводжуюча ламана лінія; дотична; spiral-shaped discretely represented curve; accompanying broken line; tangent